Anthropology and Phenomenology in Nicolás Gómez Dávila - Torregroza-Lara, Enver (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
The aim of the article is to show a new interpretation of Nicolás Gómez Dávila’s philosophy by means of an analysis of his early work Textos I. In the article it is demonstrated that the ten essays of this book, apparently dispersed, are connected thematically around the big questions of philosophical anthropology. They also can be described as phenomenological exercises from the methodological point of view. A philosophical hermeneutic of the Dávila’s work, attending different moments of his philosophy and rejecting the will to find a total system of thinking in a fragmented work, must be put forward.
Keywords: philosophical anthropology; phenomenology; colombian philosophy; Nicolás Gómez Dávila